2022
DOI: 10.3390/su14137846
|View full text |Cite
|
Sign up to set email alerts
|

Is Sport Coaching a Social Sustainable Profession for Women? Analysing the Experiences of Women Coaches in Spain

Abstract: While there are several studies showing the importance of social sustainability in different settings (e.g., Democracy and Governance: the Role of Sport Governing Bodies, urban planning, architecture) there is a lack of studies investigating social sustainability in the sports coaching profession, and even less research has specifically addressed women coaches. Using Barron and Gauntlett’s model of social sustainability (2002), the purpose of this study was to analyze the women coaches’ experiences of their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, increased exposure to women coach role models is recognised as one such way to establish greater diversity in sporting environments and encourage women to pursue a coaching career. 5 Another prominent issue for the participants was a perceived lack of respect they received relative to their male counterparts. Specifically in this study, participants reported that while respect is given to male coaches, it was believed that women coaches must prove their competency to earn respect.…”
Section: Stereotypically Male Professionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, increased exposure to women coach role models is recognised as one such way to establish greater diversity in sporting environments and encourage women to pursue a coaching career. 5 Another prominent issue for the participants was a perceived lack of respect they received relative to their male counterparts. Specifically in this study, participants reported that while respect is given to male coaches, it was believed that women coaches must prove their competency to earn respect.…”
Section: Stereotypically Male Professionmentioning
confidence: 99%
“…For example, increased exposure to women coach role models is recognised as one such way to establish greater diversity in sporting environments and encourage women to pursue a coaching career. 5…”
Section: Stereotypically Male Professionmentioning
confidence: 99%
See 1 more Smart Citation